Highly active alkyne metathesis catalysts operating under open air condition - Yanqing Ge (Nature Portfolio, 2021)
Alkyne metathesis catalysts usually suffer from high moisture/air sensitivity, which limit their wide applicability. Here, the authors report efficient alkyne metathesis catalysts that can operate under open-air conditions with a broad functional group tolerance.